Attention deficit / hyperactivity disorder , Assessment, symptoms and Homeopathy treatment for mental retardation in children - Sharma, Anil (Universal Research Reports, 2018)
ADHD is a behavioral disorder that begins in childhood, and persists into adulthood in more than half of the cases. Its basic features are inattention, impulsiveness and hyperactivity. The diagnosis based on criteria established by the Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition - DSM-V), requires the presence of at least six of nine behavioral characteristics of inattention / hyperactivity/impulsivity, which must be present for at least six months, had begun before the age of seven and these symptoms should result in a maladaptive and inconsistent functioning when compared to the developmental level. The prevalence varies from 2.2% to 17.8%, and it is likely that this variation is more related to methodological characteristics of the various studies than to geographical differences. Publications of higher methodological rigor, from all regions of the world as well as national studies, indicate a prevalence of around 5% in school age children. Studies in adults estimate the prevalence to range from 2 to 4.0% .